AAV‐delivered diacylglycerol kinase DGKk achieves long‐term rescue of fragile X syndrome mouse model - Karima Habbas; Oktay Cakil; Boglárka Zámbó; Ricardos Tabet; Fabrice Riet; Doulaye Dembele; Jean‐Louis Mandel; Michaël Hocquemiller; Ralph Laufer; Françoise Piguet; Hervé Moine (EMBO Molecular Medicine, 2022)
Abstract Fragile X syndrome (FXS) is the most frequent form of familial intellectual disability. FXS results from the lack of the RNA‐binding protein FMRP and is associated with the deregulation of signaling pathways downstream of mGluRI receptors and upstream of mRNA translation. We previously found that diacylglycerol kinase kappa (DGKk), a main mRNA target of FMRP in cortical neurons and a master regulator of lipid signaling, is downregulated in the absence of FMRP in the brain of Fmr1‐KO mouse model. Here we show that adeno‐associated viral vector delivery of a modified and FMRP‐independent form of DGKk corrects abnormal cerebral diacylglycerol/phosphatidic acid homeostasis and FXS‐relevant behavioral phenotypes in the Fmr1‐KO mouse. Our data suggest that DGKk is an important factor in FXS pathogenesis and provide preclinical proof of concept that its replacement could be a viable therapeutic strategy in FXS.